Trade and underdevelopment : a study of the small Caribbean countries and large multinational corporations - Jainarain, Iserdeo (Georgetown, Guyana : Autoprint Ltd., 1976)
The book combines theoretical analyses with case studies in an effort to look at the relationships between international trade and economic development. It also examines the usefulness of these theories in the Caribbean context of small, underdeveloped and dependent economies.
Include bibliographic index
lje 10/4/18
Loans
Keywords: Trade; Underdevelopment; Developing countries; Caribbean Area